2006
DOI: 10.1785/0120050145
|View full text |Cite
|
Sign up to set email alerts
|

Case Studies of Damage to Tall Steel Moment-Frame Buildings in Southern California during Large San Andreas Earthquakes

Abstract: On 9 January 1857, a large earthquake of magnitude 7.9 occurred on the San Andreas fault, with rupture initiating at Parkfield in central California and propagating in a southeasterly direction over a distance of more than 360 km. Such a unilateral rupture produces significant directivity toward the San Fernando and Los Angeles basins. Indeed, newspaper reports of sloshing observed in the Los Angeles river point to long-duration (1-2 min) and long-period (2-8 sec) shaking. If such an earthquake were to happen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 32 publications
(24 reference statements)
1
39
0
Order By: Relevance
“…The damage potential of longperiod shaking from a repeat of this earthquake, in particular to modern high-rise buildings in Los Angeles, has been considered in some detail (e.g., Krishnan et al, 2006). Similar concern has been noted for the potential impact of a large New Madrid Seismic Zone earthquake on tall buildings and large bridges in the central United States.…”
Section: Discussionmentioning
confidence: 92%
“…The damage potential of longperiod shaking from a repeat of this earthquake, in particular to modern high-rise buildings in Los Angeles, has been considered in some detail (e.g., Krishnan et al, 2006). Similar concern has been noted for the potential impact of a large New Madrid Seismic Zone earthquake on tall buildings and large bridges in the central United States.…”
Section: Discussionmentioning
confidence: 92%
“…The normalized histograms of slip (m) in a finite-source inversion model of the magnitude 7.9 Denali earthquake of 2002 (Krishnan et al, 2006) and one stochastic source realization using the outlined method are shown in Figure 7. The similarity in the two distributions (with the exception of the frequency of subfaults with zero slip) suggests that a series of lognormal PDFs can indeed be used to define slip distribution in stochastic source models.…”
Section: Methodology Slip Distributionmentioning
confidence: 99%
“…generated by these models against the peak velocities generated by finite-source inversions of comparable earthquakes with similar magnitudes (also simulated using SPEC-FEM3D). The finite-source inversions selected for this exercise include that of the 2002 M w 7.9 Denali fault earthquake (Krishnan et al, 2006;Fig. 15) and the 2004 M w 6.0 Parkfield earthquake (Ji, 2004).…”
Section: Application To the Southern San Andreas Faultmentioning
confidence: 99%
See 1 more Smart Citation
“…From a nonlinear time history analysis, the authors found that some 20-story models exceeded their interstory drift capacities, including models with higher strengths. Krishnan et al (2006) studied the response of a common type of building in the Los Angeles area to simulated ground motions from hypothetical magnitude 7.9 ruptures on the southern San Andreas fault. They used a fully three-dimensional building model to compare the responses of 18-story steel MRF buildings designed to the 1982 and 1997 Uniform Building Codes (UBCs).…”
Section: Introductionmentioning
confidence: 99%